PENGARUH INOVASI DAN INFORMASI TERHADAP KINERJA (STUDI PADA UMKM DI KOTA BANJARMASIN) - Sulastini Sulastini; Fariansyah Fariansyah; Husnurrofiq Husnurrofiq (JURNAL BISNIS DAN PEMBANGUNAN, 2021)
The long-term objective of previous research that has focused on issues of innovation and information in manufacturing companies and service companies. Research conducted at companies including Anttila J., Jussila K., 2018, Ramayah T. While in this study focused on research conducted at UMKM Banjarmasin City. and information partially has a significant effect on the performance of MSMEs. Analyzing and knowing innovation and information simultaneously have a significant effect on the performance of MSMEs. Based on the observations of researchers, the problem is that innovation and information have not been optimal on the performance of MSMEs. This research method uses a quantitative approach. This research is an expalanatory research, namely testing the influence between the variables of innovation, information, while the dependent variable is the performance of MSMEs, data collection techniques conducted by researchers, namely interviews, questionnaires, and documentation. Hypothesis Testing. The statistical method used is multiple regression. The results of this study prove that innovation has a significant effect on the performance of MSMEs of 0.350. The results of this study also indicate that information has a significant effect on the performance of MSMEs of 0.388. Innovation and information simultaneously have a significant effect on the performance of MSMEs of 0.537. This study aims to provide information that better interactions and relationships are a side effect of providing space for MSMEs.Keywords: Innovation, Information, UMKM’s Performance